"There Should Have Been a More Holistic Approach"—A Qualitative Study of Young Adult Cancer Survivors' Experiences of Follow-up After Cancer Treatment. Issue 1 (22nd January 2022) - Aase, Andrea S.; Ingebretsen, Thea K.; Hauken, May Aa.
Abstract : Background: Young adult cancer survivors (YACSs) are in a vulnerable period of life with increased risk of severe physical and psychosocial late effects. However, limited research exists on follow-up of YACSs after cancer treatment. Objective: The aim of this study was to explore how YACSs experience follow-up from the healthcare system after finishing cancer treatment. Methods: Using a qualitative method with an interpretive descriptive design, 20 YACSs were interviewed 4 times over a period of 6 months. The transcribed interviews were analyzed using Systematic Text Condensation. Results: Four main themes were identified: "They should have prepared me better, " "The GP (general practitioner) does not understand my challenges, " "My check-ups are all about cancer relapse, " and "I do not know who's in charge." Conclusion: The findings indicate deficiency in the healthcare system's follow-up of YACSs in terms of preparation for the survival phase, interdisciplinary cooperation, and acknowledgement of late effects, as well as organization of follow-up care within the healthcare system. Implications for Practice: A more holistic perspective on follow-up care that addresses YACSs' multidimensional challenges is suggested, including a multidisciplinary approach where cancer nurses should play an active role.